2017
DOI: 10.1021/acsomega.7b00955
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic SO3 Decomposition Activity and Stability of Pt Supported on Anatase TiO2 for Solar Thermochemical Water-Splitting Cycles

Abstract: Pt-loaded anatase TiO 2 (Pt/TiO 2 -A) was found to be a highly active and stable catalyst for SO 3 decomposition at moderate temperatures (∼600 °C), which will prove to be the key for solar thermochemical water-splitting processes used to produce H 2 . The catalytic activity of Pt/TiO 2 -A was found to be markedly superior to that of a Pt catalyst supported on rutile TiO 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
3
25
1
Order By: Relevance
“…A reference catalyst, K–V–O/SiO 2 was also prepared in a similar manner. Another reference catalyst, 1 wt % Pt/TiO 2 , was prepared by impregnation using an aqueous solution of Pt­(NO 2 ) 2 (NH 3 ) 2 (Tanaka Precious Metals) and anatase TiO 2 (JRC-TIO-8, supplied by Catalysis Society of Japan), as reported previously . Prior to catalytic measurement, all the catalysts were aged under the catalytic reaction atmosphere (14 vol % SO 3 , 18 vol % H 2 O, and N 2 balance) for 3 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reference catalyst, K–V–O/SiO 2 was also prepared in a similar manner. Another reference catalyst, 1 wt % Pt/TiO 2 , was prepared by impregnation using an aqueous solution of Pt­(NO 2 ) 2 (NH 3 ) 2 (Tanaka Precious Metals) and anatase TiO 2 (JRC-TIO-8, supplied by Catalysis Society of Japan), as reported previously . Prior to catalytic measurement, all the catalysts were aged under the catalytic reaction atmosphere (14 vol % SO 3 , 18 vol % H 2 O, and N 2 balance) for 3 h.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that two classes of materials are candidates for active SO 3 decomposition catalysts that work at around 600 °C. One is precious metals, the following sequence of their activities was reported: Pt > Pd > Rh > Ir > Ru. , Because metallic Pt promotes the dissociation of adsorbed SO 3 into SO 2 and O and the subsequent desorption these decomposition products most efficiently, supported Pt catalysts are promising for the required temperature range. , Stable Pt catalysts can be prepared by depositing Pt onto SO 3 -resistant support materials, including TiO 2 , ,,, SiO 2 , , SiC, and Ta 2 O 5 . Although these supported Pt catalysts demonstrate excellent catalytic activities, their widespread use should be limited due to the high cost and rarity.…”
Section: Introductionmentioning
confidence: 99%
“…5(a)]. 33) At this temperature, Pt is mainly present in the active metallic state on anatase TiO 2 , whereas less-active Pt oxides (PtO 2 and PtO) are dominant on rutile TiO 2 . This stark contrast can be attributed to the greater interfacial formation energy, which stabilizes the oxidized states of Pt on rutile.…”
Section: Pgm Catalystsmentioning
confidence: 95%
“…The increased activity of Pt on anatase is related to the abundance of metallic platinum, which facilitates the dissociative adsorption of sulfur trioxide as well as SO 2 and O 2 removal from the surface. A slight activity loss has been observed in these catalysts attributed to the slow sintering and loss of platinum [130]. The catalytic activity of non-platinum-based catalysts has also been studied.…”
Section: Green Hydrogen Technologiesmentioning
confidence: 99%